2018
DOI: 10.1097/igc.0000000000001174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of F-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Scanning in the Staging of Patients With Stage IIIB Cervical Carcinoma and the Impact on Treatment Decisions

Abstract: Fluorodeoxyglucose PET/CT is useful in assessing distant disease and evaluating nodal involvement in patients with invasive cervical cancer. Additional findings on the PET/CT that were missed by conventional imaging and clinical examination caused treatment change in a significant proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Challenges with clinical staging include the inadequate evaluation of the proximal tumour extension or side wall invasion, and inaccurate lymph node evaluation (especially deep pelvic lymph nodes). [68] With a sensitivity and specificity of lymph node evaluation of 100% and 99.6% respectively for nodes larger than 5mm, and the ability to detect metabolic changes before anatomical changes occur,[69,70] 18 F-FDG PET/CT is more effective at detecting lymph node involvement,[68] distant metastases,[71] and tumour activity. [72] LDC in our study included lymph nodes within the radiation field as visualised on 18 F-FDG PET/CT scans and we report on the loco-regional metabolic response, not the clinical response of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges with clinical staging include the inadequate evaluation of the proximal tumour extension or side wall invasion, and inaccurate lymph node evaluation (especially deep pelvic lymph nodes). [68] With a sensitivity and specificity of lymph node evaluation of 100% and 99.6% respectively for nodes larger than 5mm, and the ability to detect metabolic changes before anatomical changes occur,[69,70] 18 F-FDG PET/CT is more effective at detecting lymph node involvement,[68] distant metastases,[71] and tumour activity. [72] LDC in our study included lymph nodes within the radiation field as visualised on 18 F-FDG PET/CT scans and we report on the loco-regional metabolic response, not the clinical response of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical imaging for treatment planning has been used for a long time, but has limited sensitivity in determining the stage of cancer and low ability to determine the biology of the tumor and healthy tissue. Molecular imaging allows to assess the distribution of the molecular vector that represents the biological process, and thus better defines the area of external beam irradiation [12]. Ma et al proved that there are significant differences in tumor volume between images obtained with 18 F-FDG-PET/CT and MRI, probably resulting from the cervical and endometrial position, as well as the filling of the bladder and rectum [8].…”
Section: Discussionmentioning
confidence: 99%
“…The staging of cervical cancer is based on the FIGO (International Federation of Gynecology and Obstetrics) classification, which is a clinical staging system involving a thorough clinical examination and anatomical imaging. In a resource-constrained setting, a chest x-ray, abdominal ultrasonography, and cystoscopy are routinely performed on patients with cervical cancer with further investigations considered on a case-by-case basis, and depending on resources and availability (5).…”
Section: Introductionmentioning
confidence: 99%
“…Morkel et al reported that the addition of 18 F-FDG PET/CT to the initial screening protocols for patients with FIGO stage IIIB cervical cancer revealed relevant disease information that was missed by clinical staging and other imaging techniques. The information gathered from the 18 F-FDG PET/CT resulted in a change in treatment protocols in a significant number of patients with cervical cancer (5). In a study by Kidd et al, 53% of the 234 patients with cervical cancer (FIGO stage IB1–IVA), had FDG-avid lymph nodes on 18 F-FDG PET/CT scans, with nodes visualized as high as the supraclavicular region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation